Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran di Provinsi Kalimantan Timur - Kurniawan, Aboy; Musa, Adnan Haris; Suharto, Rachmad Budi (FORUM EKONOMI, 2017)
The purpose of this study was to determine the effect of population, inflation and investments in open unemployment in the province of East Kalimantan. The method or tool of analysis used in this research is multiple regression analysis approach to the classical assumptions are processed in a detailed explanation. This study uses secondary data obtained from the Central Statistics Agency (BPS). From the results of data analysis that I do can be concluded that: (1) Large population can move the market in terms of demand through the multiplier effect due to the aggregate demand is high. (2) From the results it is observed that there is a close relationship between inflation and unemployment. (3) The size of investments that occurred in the community will greatly affect the size of employment opportunities created.Keywords: Regression Analysis, Population, Inflation, Investment, Unemployment.